Impact of high hemoglobin levels on carotid artery intima–media thickness and its predictive value for hypertension in high-altitude areas: a real-world study - Long Hongyu; Long Ga; Zhang Yiqian; Xu Qiuyu; Li Kemin; Qing Maiyongcuo; Xiong Min (Frontiers in Cardiovascular Medicine)
Background and purposeThe hemoglobin levels in the peripheral blood of individuals living at high altitudes are significantly higher than normal levels. These levels are closely associated with atherosclerosis and cardiovascular events. This study aimed to investigate the correlation between hemoglobin levels in the peripheral blood and hypertension in high-altitude regions, providing a basis for preventing and treating primary hypertension in these regions.Materials and methodsFrom May 2020 to May 2021, patients diagnosed with primary hypertension in plateau regions of China were selected as participants. The clinical data, including lifestyle habits and blood biochemical indicators, were collected from the clinical case database for patients meeting the inclusion criteria. The logistic regression analysis was performed to identify factors influencing carotid intima–media thickness in patients with primary hypertension in plateau regions. The ROC curve was plotted to analyze the impact of peripheral blood hemoglobin levels on hypertension, determine the hemoglobin threshold for predicting hypertension in plateau areas, and evaluate the predictive value of hemoglobin level for hypertension.ResultsA total of 200 patients (105 men with an average age of 64.8 ± 12.75 years and 95 women with an average age of 69.5 ± 11.54 years) were enrolled in this study. Logistic regression analysis revealed that age, CO2-CP, ALT, APOB, CRP, and HGB were independent risk factors for increased carotid artery intima–media thickness (P < 0.05). The hemoglobin threshold for predicting hypertension in high-altitude areas was 131 g/L. The area under the ROC curve for predicting hypertension with elevated hemoglobin level was 0.799 (0.719–0.880).ConclusionElevated hemoglobin levels contribute to the thickening of the carotid artery intima–media layer and hold predictive value for high-altitude hypertension.